Effects of high altitude and nutritional status over the physical fitness of young Nepalese residing in Pokhara, Kaski district of western Nepal (South East Asia Journal of Public Health, 2013)
Pokhara is situated over 5,577ft above sea level in The Kingdom of Nepal. Such high-hilly regions of Nepal contain only one-third as much oxygen as sea level air and in order to acclimatize to such environmental hypoxia, a series of metabolic and musculocardio-respiratory adaptations initiate that influence oxygen transport and utilization, which is necessary to achieve optimal physical performance at altitude. The health of people residing at such high altitude is determined not only by the environment but also by means of nutritional determinants. The present study was conducted to explicate the effect of high altitude environment with nutritional factors over physical fitness of young Nepalese of Pokhara. Twenty-five male young Nepalese were randomly selected from Pokhara, Nepal (mean age 21.6) and twenty-five sedentary college students of Kolkata, India (mean age 21.9) were taken as controls. Results showed a significant difference in BMI, body fat percentage, pre- and post-exercise BP, PFI, VO2max, energy expenditure and anaerobic power (P